Downregulation of CIC Does Not Associate with Overexpression of ETV1 or MAP Kinase Pathway Activation in Gastrointestinal Stromal Tumors. (9th August 2014) - Schoppmann, Sebastian F.; Ricken, Gerda; Ilhan-Mutlu, Aysegül; Nirtl, Nadine; Streubel, Berthold; Preusser, Matthias; Birner, Peter
Abstract : ETV1 is a key factor in gastrointestinal stromal tumors (GIST), and is promoted by CIC downregulation in melanoma. We investigated CIC, ETV1, and the MAPK pathway in GIST. Downregulation of CIC protein levels as assessed by immunostaining was seen in 17/144 GIST, but was not associated with ETV1 or pMEK1/2 expression, KIT and PDGFRA mutations, copy number variations (CNV) of 19q13, and clinical factors. However, the data indicate that the incidence of CIC downregulation may differ for GISTs in different locations in the gastrointestinal tract, and that CNV of 19q13 is associated with shorter disease-free survival.